SUBKLİNİK NÖROSARKOİDOZUN EMG İLE ERKEN TANISI - YANARDAĞ, Halil; BİLİR, Muammer; KIZILTAN, Meral; SiPAHi, Sevtap; ÇAĞATAY, Tülin; DEMİRCİ, Sabriye; KARAYEL, Tuncer (Cerrahpaşa Medical Journal, 2014)
Background and Design. Although lungs, lymph nodes, liver, and eye are the most involved sites in sarcoidosis, which is a chronic granulomatous disease of unknown etiology, 510% of patients have symptoms related to central nervous system (CNS) involvement. Nevertheless, subclinic CNS involvement is more common 15% of sarcoidosis patients in necropsy. Peripheral nerve and muscle involvement in subclinic and/or undiagnosed neurosarcoidosis can be detected by electromyographic (EMG) studies in early stage of the disease. In this study, 44 sarcoidosis patients without symptoms of neurosarcoidosis were examined for peripheral nerve and/or muscle involvement by EMG. Five of patients were male and 39 were female (mean age=38±13). Results. In 18 patients (40.9%) motor conduction velocities were found to be slowed. In five of these, the slowing was localised in both lower extremities and symmetric, whereas in 13 patients it was asymmetric and restricted to one nerve. In ten out of 13 patients, it was localised in lover extremities. In two out of 3 patients with upper extremity involvement, lower extremities were also involved. The conduction abnormalities could be considered as mild to moderate regarding the mean age of patient population and they did not exceed the limit of demyelinating neuropathies. The highest figure for peripheral neuropathy in sarcoidosis reported from previous studies is 22.2%. In 14 patients; slowing in sensorial distal conduction velocities and/or reduction in amplitudes of median nerve were detected and considered as compatible with carpal tunnel syndrome. Because there is no previous report on the relationship between carpal tunnel syndrome and sarcoidosis, this finding was interpreted as irrelevant regarding the mean age and gender distribution of our patient group. In 8 patients myographic involvement was detected by concentric needle EMG, therefore in 31 patients electromyographic abnormality was found. Conclusion. Our results suggest that peripheral nerve involvements are frequent in sarcoidosis patients without neurological sings and symptoms and therefore electromyographic studies should be made in these patient population in early stages.